2021
DOI: 10.1088/1755-1315/882/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

Removal of mercury ion from wastewater using natural zeolite: effect of humic acid to adsorption isotherm

Abstract: As Indonesia possessed a considerable amount of gold deposit, many golds mining activities, including the small-scale one, is commonly found. A simple mining technique (amalgamation) that utilizes mercury (Hg) will generate mercury-containing wastewater. One of the prospective Hg removal methods from wastewater is adsorption. In addition, it is also possible that metal contained in the wastewater interacts with other substances, such as humic acid. This experiment was aimed to examine the adsorption process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, compared to modal solutions, obtained leachates comprise of various organic and inorganic mercury species, which significantly affect mercury uptake. For instance, it was found that mercury uptake onto natural zeolite was hindered by the presence of humic acids, due to its partial sorption to organic matter [74]. Removal of mercury from industrial effluents (0.0028-0.0246 mg Hg/kg) resulted in lower capacity of natural zeolite in the range 0.0039-0.021 mg/kg, due to the competition of other present cations, which also undergo sorption on zeolite [75].…”
Section: Mercury Leaching From Contaminated Soil and Its Subsequent S...mentioning
confidence: 99%
“…Furthermore, compared to modal solutions, obtained leachates comprise of various organic and inorganic mercury species, which significantly affect mercury uptake. For instance, it was found that mercury uptake onto natural zeolite was hindered by the presence of humic acids, due to its partial sorption to organic matter [74]. Removal of mercury from industrial effluents (0.0028-0.0246 mg Hg/kg) resulted in lower capacity of natural zeolite in the range 0.0039-0.021 mg/kg, due to the competition of other present cations, which also undergo sorption on zeolite [75].…”
Section: Mercury Leaching From Contaminated Soil and Its Subsequent S...mentioning
confidence: 99%